Pengaruh Gaya Kepemimpinan Servant Leadership, Budaya Perusahaan, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Anis Jauharotul Farida; Hadi Sunaryo; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTEmployee job satisfaction is one of the important things for a company. Because if employees feel satisfied with their work, then the services provided to customers will also get better, and it will trigger an increase in sales. This research aims to determine the influence of leadership style servant leadership, company culture, and work environment on PT Karya employee job satisfaction Giri Palma. This study uses a sample of 56 employees from a population of 126 employees. The sampling technique used in this study is using purposive sampling technique using the Slovin formula. The sample used is employees who do not work outside the office of PT Karya Giri Palma. Based on the results of research that has been done, it is obtained that the variables of servant leadership style, company culture, and work environment significantly influence employee job satisfaction. The servant leadership style does not significantly influence employee job satisfaction. Corporate culture does not significantly influence employee job satisfaction. The work environment has a significant effect on employee job satisfaction.Keywords : Servant Leadership Leadership Style, Corporate Culture, Work Environment, Employee Job Satisfaction